Curriculum Reconstruction Based on Graduate Profile to Strengthen Managerial Competence in the Chemistry Education Study Program - Farwati, Ratna; Siti Marfu’ah; Riska A Syahputri; Rohana Asmawati; Nabela; Ummu Kalsum (Orbital: Jurnal Pendidikan Kimia, 2025)
The alignment of the Chemistry Education Study Program curriculum structure at UIN Raden Fatah Palembang with the graduate profile as educational institution managers was evaluated in this study, and recommendations for curriculum reconstruction based on the graduate profile were developed. Despite growing demands for graduates who can take managerial roles in educational institutions, little empirical evidence exists on how undergraduate chemistry education curricula allocate credits, learning experiences, and assessment to develop managerial competence — this study addresses that gap. A qualitative case study approach was employed, in which curriculum documents, tracer study data, questionnaires, and interviews were analyzed for data triangulation. Of the total 146 credits in the curriculum, only 16 credits were found to explicitly support managerial competencies. The tracer study (n = 165 respondents) indicated that 16.4% of alumni were employed in educational institution management. A mismatch was identified between the formulation of graduate profiles and the allocation of curricular content, along with limited implementation of project-based learning and managerial internships. Recommendations were proposed, including: (1) the inclusion of courses on educational management and leadership; (2) the strengthening of project-based learning and MBKM internships within managerial pathways; (3) the application of authentic assessment and portfolio evaluation to measure managerial competence; and (4) the development of a phased blueprint for curriculum reconstruction. To our knowledge, this study’s novel contribution lies in empirically linking curriculum mapping, alumni tracer outcomes, and pedagogical practice to produce a context-specific, phased blueprint and concrete recommendations for a graduate-focused chemistry curriculum.